Diagnostic performance of the Enferplex bovine tuberculosis antibody test using bulk tank milk samples from dairy cattle - Alastair Hayton; Amanda O'Brien; Andy Adler; Keith Cutler; John Clarke; Darren J. Shaw; Neil J. Watt; Gordon D. Harkiss (Journal of Dairy Science)
ABSTRACT: Bovine tuberculosis, caused mainly by Mycobacterium bovis, is a major disease of cattle worldwide associated with significant economic losses and is usually diagnosed using periodic tuberculin skin tests, IFNγ release assay, or at postmortem. Recently, we developed a multiplex test for detecting antibodies to Mycobacterium bovis in cattle that has high sensitivity and specificity using serum or individual milk samples. Here, we assessed the performance of the test using bulk tank milk samples from skin test–positive and bovine tuberculosis–free cattle herds. In nonanamnestic bulk tank milk samples, the sensitivity relative to the comparative cervical skin test was 77.2% and the specificity was 99.8% using the high sensitivity setting of the antibody test. A kappa value of 0.85 was found, indicating almost perfect agreement between the test results and comparative cervical skin test status of the herds. Likelihood ratio analysis gave a positive likelihood ratio of 53.1 and a negative likelihood ratio of 0.030, indicating that the test provides good diagnostic evidence of the infection being either present or absent, respectively. Bulk tank milk samples from herds with inconclusive reactors to the comparative cervical skin test but had no reactors gave a test positivity of 73.7%, indicating that antibody-positive animals were present in the herd after removal of the reactors. Variances in herd prevalence did not result in statistically significant differences in test positivity, and the test was able to detect a herd prevalence of 0.1% of comparative cervical skin test reactors in 80% of low prevalence herds. The test showed good repeatability and reproducibility, giving complete concordance in results from 3 independent laboratories. The results show that the bulk milk antibody test could be used as a nonanamnestic surveillance tool for detecting and monitoring bovine tuberculosis in dairy cattle herds.